Self-other agreement in DSM-5 Section III Dimensional Personality Traits: A study on Italian community individuals. (1st August 2018) - Bottesi, Gioia; Ghisi, Marta; Martignon, Anna; Sica, Claudio
Abstract: Integrating self- and other-reports allows gaining complementary information while assessing personality traits of a target individual. The current study aimed at exploring self-other agreement in personality through the Personality Inventory for the DSM-5 (PID-5) and the PID-5-Informant Form (PID-5-IRF) in an Italian community sample. Data from 80 pairs (80 targets and 80 informants) were collected. Informants were spouse/life partners, dating partners, family members, and friends. Targets completed the PID-5, whereas informants filled-in the PID-5-IRF. Data collection was performed through two different online surveys - one for targets and one for informants. Overall, self-other agreement was moderate and its association with duration and perceived closeness of acquaintanceship was almost negligible. Self-other agreement was higher when informants were spouse/life or dating partners than when they were family members or friends. Implications of present findings are discussed along with recommendations for future research. Highlights: Self-other agreement for the PID-5 domains and facets is, overall, moderate. Duration and perceived closeness of acquaintance are unrelated to self-other ratings. Self-other agreement is higher when informants are romantic partners.